Impact of solar pre-drying and yeast starter inoculation treatments on volatile compounds in cocoa (Theobroma cacao L.) beans from Southwestern Colombia - Juan Florencio Tejeda; Jessica Arango-Angarita; Jairo Leonardo Cuervo (Applied Food Research, 2024)
In the region of Tumaco (Nariño, Colombia), in Southwestern Colombia, the CCN-51 cocoa clone has been commonly cultivated in recent decades. Determining the influence of cocoa processing conditions (pre-drying and yeast starter inoculation) on the profile of volatile compounds is essential to ensure maximum cocoa quality. To this aim, cocoa beans were fermented following four different treatments: (1) spontaneously (at room temperature for 120 h) in traditional conditions (control; CO); (2) traditional processing with a pre-drying (sun-dried for 24 h) treatment (PD); (3) with fermentation (for 120 h) after inoculation of a yeast starter culture (YS); and (4) including both treatments, pre-drying and yeast inoculation (PD+YS). A total of 45 volatile compounds were identified by SPME-HS/GC–MS and classified as: alcohols (9), aldehydes and ketones (17), acids (6), esters (3), pyrazines (2), aliphatic hydrocarbons (4) and others (4). Pre-drying and yeast starter inoculation reduced the concentration of acids, which are associated with off-flavour notes. Fermentation with a selected yeast culture generated desirable flavour notes (sweet, fruity, floral, buttery and malty). The PCA score plot showed a clear separation of the samples obtained from the different treatment studied. In conclusion, pre-drying and inoculating with selected yeasts during processing help enhance the sensory quality of the cocoa.